Solutions for Cyber-Physical Systems Ubiquity - Druml, Norbert, 1980- (Hershey, USA: Engineering Science Reference (an import of IGI Global), 2018)
"This book contains a collection of latest results and insights of state-of-the-art solutions for CPS ubiquity, with a specific focus on the Internet-of-Things. It provides an overview of current developments and future trends in this area"--
Includes bibliographical references (pages 424-468).
Keywords: Cooperating objects (Computer systems) -- Handbooks, manuals, etc; Internet of things -- Handbooks, manuals, etc; Automatic control -- Handbooks, manuals, etc